An Analysis of Using Prepositional Phrase in Students’ Writing - Moh Yusril Jaya; Siska Bochari; Hastini Hastini; Ferry Rita (Universitas Cokroaminoto Palopo, 2023)
Prepositional phrase is a group of words consisting of a preposition and its object that modify the object. This research focused on prepositional phrase that found on students’ writing made by fifth semester students of English Education Study Program, Tadulako University. The objectives of this research were to identify functions of prepositional phrase occur in the students’ writings and to find out the most dominant prepositional phrase used by the students in their writing. This research used descriptive qualitative design. The subject of this research was 10% of total subject (about 19 students). The subject was chosen by using purposive sampling technique. The data of this research were the sentences contain prepositional phrase in students’ writings. Based on the theory used, the researchers identified the functions of prepositional phrase in the data, and discovered the most dominant function of prepositional phrase. From the analysis, there are two functions of prepositional phrase found in the students’ writings. They are complement and adjunct. If it is adjunct, it can be adjectival adjunct and adverbial adjunct The most dominant function is complement which is 62%.